تحسين أداء ورفع كفاءة حساس القوة لقياس الوزن بمساعدة دارة جسر كامل - عبد الهادي القصاص (Tishreen University, 2018)
In engineering applications, electrical measurement of mechanical quantities can often be found. It is also widely used in engineering applications force measurements, using strain gauge which is one of the most popular transducers in measuring strain. A strain of mechanical element can be found due to stress because of influence of applied external forces which made a deformation on the form of the element, but it is necessary to observance elastic of the element. Applied force causes tiny differences in resistance of strain gauge. To accurate measurements and increasing sensitivity during measure, this research present how to employ four strain gauge elements, electrically connected to form a Wheatstone bridge circuit. After a theory about forces on mechanical element, knowing configuration of strain gauge and how to measure force using a half bridge circuit which doesn't give accurate results because of low sensitivity. Developing strain gauge conjunction with various measuring circuits, especially in Wheatstone bridge configuration to raise measurement efficiency, which is the goal of this research. في بـــــــعض التطبيقات الهندسية كثيرا ما يتم التعامل مع المقاديـــر الميكانيكيــة التي يــــكون من الضروري قياسها كهربائيــا، وتكون القـــوة من أحد المقــاديــر الفــيزيائيــة القابلــة للقياس كهــربائيــاً بـاستخدام مقيـاس التشـوه   (strain gauge)الذي يكون من أكثر محولات القياس شيوعا في قياس الانفعال (strain).ينتج انفعال عنصر ميكانيكي بسبب الإجهاد الذي يتعرض له تحت تأثير قوى خارجية مطبقة تؤدي إلى تشوه شكل العنصر، ولكن يجب مراعاة قدرة تحمل العنصر للقوى المطبقة ضمن حدود الأمان حتى لا يفقد مرونته. تؤدي القوة المطبقة إلى تغييرات صغيرة جداً في مقاومة مقياس التشوه ومن أجل قياسات دقيقة وزيادة الحساسية أثناء القياس يقترح هذا البحث استخدام أربعة مقاييس تشوه متصلة كهربائياً لتشكيل دارة جسر واتستون(Wheatstone bridge)، وذلك بعد إجراء دراسة نظرية عن القوى المؤثرة على عنصر ميكانيكي، والتعرف على تصميم مقياس التشوه، وكيفية قياس القوة باستخدام دارة نصف جسر التي لا تعطي نتائج قياس دقيقة نظراً للحساسية المنخفضة، وتطوير كيفية وصل مقياس التشوه مع مختلف دارات القياس، خاصةً في تكوين جسر وتستون لرفع كفاءة القياس وهو ما يعتبر هدف هذا البحث.